PERAN POS BANTUAN HUKUM (POSBAKUM) DI PENGADILAN AGAMA BENGKULU KELAS I A BERDASARKAN PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2014 - Prabowo, Ari (UIN Fatmawati Sukarno Bengkulu, 2017)
The purpose of this research is to know the Role of Post of Legal Aid (Posbakum) based on Supreme Court Regulation Number 1 Year 2014 and implementation of Posbakum in serving the justice seeking society that can not afford in Religious Court of Bengkulu Class I A. Research conducted at Bengkulu City Court, at March-June 2017. The research method used is survey method and data retrieval technique done by library study and open interview. Data were analyzed descriptively qualitative. The result of this research is expected to have social value which is giving information to Bengkulu people in particular, and society (nation) Indonesia generally about the benefits or the power of Legal Aid to the poor people in Religious Court of Bengkulu Class I A.